Pro dan Kontra Kepemimpinan Islam di Indonesia - Wahidah Rangkuti; Ildan Saleh; Reski Hidayah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research examines the pros and cons of Islamic leadership in Indonesia, a complex issue amidst the social and political diversity of a country with the largest Muslim population in the world. With a qualitative approach, this research explores various perspectives regarding the application of Islamic values ​​in leadership, which are considered to provide moral guidance and strengthen national identity. However, there are also concerns regarding the potential exclusion of non-Muslim groups and the disregard for the principles of democracy and pluralism. Through literature analysis, this research concludes the need for interfaith dialogue and political education that emphasizes religious harmony to create inclusive and just policies, so as to bridge Islamic values ​​with the needs of diverse communities.